Assessment Of DNA Repair Gene Expressions In Vitrified Mouse Preantral Follicles - Zahra Khodavandpour (Cell Journal, 2020)
Objective Vitrification of the ovarian tissue is one of the techniques recommended for preserving the fertility of women who are dealing with infertility. Despite its benefits, our information about the molecular aspects of ovarian follicles vitrification is somehow ambiguous. Therefore, the aim of this study was to evaluate the expression pattern of DNA repair genes in vitrified preantral follicles.